The Relationship between the Character of Mutual Cooperation and Global Diversity and Students' Pancasila Education Learning Achievement - Kharismadewi, Kadek Pasek Satya; Astawan , I Gede; Trisna, Gusti Ayu Putu Sukma (Jurnal Pendidikan Multikultural Indonesia, 2024)
The problem of declining student character scores in elementary schools has an impact on students' Pancasila Education learning achievement. Based on the results of the interview, teachers are hampered in instilling character values in students because of the diversity of student characteristics. This research aims to analyze the relationship between the character of mutual cooperation and global diversity and students' Pancasila Education learning achievement. This research is an ex post facto study with the research population, namely all fifth grade elementary school students and 89 students as the research sample. Data obtained through non-test methods were analyzed using descriptive analysis and inferential analysis. The results of inferential analysis using multiple linear regression analysis show that the correlation coefficient test results obtained are rcount = 0.298 which is greater than rtable = 0.207 which shows that there is a significant relationship between variables X1 and X2 and variable Y. The coefficient of determination is obtained shows a contribution of 8.9% of the Pancasila Education learning achievement variable which is determined by the students' globally diverse character. From the data analysis, it can be concluded that there is a significant relationship between the character of mutual cooperation and global diversity and the Pancasila Education learning achievement of fifth grade elementary school students.